PRAKTIK PENGELOLAAN KEUANGAN DAN TANTANGAN KEBERLANJUTAN USAHA PETANI BUDIDAYA RUMPUT LAUT DI KABUPATEN BIMA - Siti Ahdina Saadatirrohmi; Lisnawati (Yayasan Nusantara Hasana Berdikari, 2026)
Seaweed cultivation is an economic sector that plays a crucial role in improving the welfare of coastal communities. However, the success of a cultivation business is not solely determined by production but also by the ability of entrepreneurs to manage their finances. This study aims to analyze financial management practices and identify challenges faced by seaweed farmers in Laju Village, Langgudu District, Bima Regency. The study employed a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The informants consisted of purposively selected seaweed farmers. Data analysis employed the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. The results indicate that farmers' financial management practices remain rudimentary, characterized by manual financial record-keeping, a lack of separation between business and household finances, and a lack of systematic financial planning. Key obstacles include fluctuating seaweed prices, limited capital, low financial literacy, limited access to formal financial institutions, and environmental factors that impact production output. This study suggests that improving financial literacy, strengthening access to financing, and training in simple financial record-keeping are necessary to enhance the sustainability of seaweed cultivation businesses.